Historical Dictionary of Shinto. - Picken, Stuart D. B. (Rowman & Littlefield Pub. Group, 2011)
One of Japan's major religions, Shinto has no doctrines and there are no sacred texts from which religious authority can be derived. It does not have an identifiable historical founder, and it has survived the vicissitudes of history through rituals and symbols rather than through continuity of doctrine. Shinto is primarily a religion of nature, centered on the cultivation of rice, the basis of a culture with which the western world is not familiar in terms of either its annual cycle or the kind of lifestyle it generates. The roots of the Shinto tradition probably precede this and reflect an a.